Perbandingan Kinerja Protocol Routing Open Shortest Path First (OSPF) dan Routing Information Protocol (RIP) Menggunakan Simulator Cisco Packet Tracer - Wahyu Sasongko Jati; Heru Nurwasito; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Routing is very important for the process of taking a packet from a device and sending it through the network to another device on a different network. The routing algorithm affects the sending process of a packet and also the network that exists on the routing. In a network topology to transmit data is used a variety of routing protocols. OSPF with link-state algorithms and RIP using distance vector algorithms is the most of popular used routing protocols. This study was conducted to compare the performance of the OSPF and RIP routing protocols on LAN networks. By comparing and analyzing the required travel time of the routing protocol in sending a number of different data packets, we can know which routing protocol is the fastest on topology that has been designed. From the results of the study can be concluded that the OSPF routing protocol faster in the delivery of data packets by looking at the results of the travel time required to deliver a specified number of data packets.